Pola Asuh Orang Tua dan Implikasinya terhadap Prestasi Akademik Siswa Sekolah Dasar Yang Berkegiatan di TPA Alba - Fitria, Heni; Burhanuddin , Afid; Purnamasari, Mega Isvandiana (Scholarly Journal of Elementary School, 2022)
This study aims to determine: (1) the parenting parents elementary school students who study in TPA ALBA, (2) the implication of parenting parents elementary school students who study at TPA ALBA toward academic achievement of students.This research is a qualitative descriptive study using 6 subjects selected by purposive sampling on students who study at TPA ALBA. The object of this study is parenting and its implications for students’ academic achievement. Data collection techniques used observation, interviews, and documentation. Data analysis used in this research was data reduction, data display, and conclusion drawing.The result of the data analysis can be concluded that: (1) Parenting style with authoritative type has a positive impact on children’s development. (2) Parenting style with authoritative type becomes a factor as an improvement student’s academic achievement.